A Daylength Recognition Model of Photoperiodic Flowering - Wang, Xiaoying; Zhou, Peng; Huang, Rongyu; Zhang, Jianfu; Ouyang, Xinhao (Frontiers in Plant Science, 2021)
The photoperiodic flowering pathway is crucial for plant development to synchronize internal signalling and external seasons. One hundred years after the photoperiodic flowering phenomenon was discovered, the core signalling network for photoperiodic flowering has been elucidated in model plants such as Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa), and soybean (Glycine max). Here, we review the progress of the plant photoperiodic flowering area and summarize the previously accepted photoperiodic flowering models. We then introduce a new model based on daylength recognition by florigen. By determining expression of the florigen gene, this model can assess the mechanism of daylength sensing and crop latitude adaptation. Future applications of this model under global climate change are discussed.